Are we getting the message across? Trends among young men attending an inner city young people's clinic. Issue 6 (30th November 2004) - Armitage, C; Curran, B; Wright, S; Lenehan, K; Kell, P
Abstract : Background: A young people's clinic has been running at the Archway Sexual Health Clinic since 1997. This offers a weekly walk-in service to both young men and women under 20 years old. Objectives: To review the audit data of over 7 years' experience from the dedicated young people's clinic at the Archway Sexual Health Clinic, the "Arch." Methods: These data were collected by retrospective notes review of a consecutive series of all male attendees over a 7 year period from 1997 to the end of 2003 with collection of data in Microsoft Excel database. Results: These figures show an overall increase in attendee numbers, but also a relative rise in the numbers of young men using the service. A high number of bacterial sexually transmitted infections were detected. In 2001 and 2003 respectively, 14.5% and 17.8% of the young men using the service were diagnosed with Chlamydia trachomatis . A user survey aimed to identify factors that may be encouraging the young men to access the service. Conclusions: Responding to the views of young men using the service has played a part in service development. Initiatives at the "Arch" such as the condom policy and choice of gender of staff may be factors encouraging increasing attendances. Continuing to work with other agencies to develop ways to engage young men are recommended. Word of mouth recommendation cannot be underestimated in publicising the service.